Comparative labor force analysis in conventional and ecological agriculture: Oleaginous plants - Ionut Laurentiu Petre (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
This paper seeks to analyse from a comparative point of view the efficiency of the use of manual labour as well as the mechanized works in the cultivation of oil plants in order to obtain profit and the profitability of this activity from the point of view of conventional and ecological crops. The main source of data to be analysed in this paper was the technical reports submitted by the Research Institute for Agriculture Economy and Rural Development through the ADER 13.1.2 project to the Ministry of Agriculture and Rural Development, data referring to the technological value of the three crops (sunflower, rape, soybean) but also with reference to the income and expenditure budget. These data are calculated per unit area and one hectare respectively. Finally, the efficiency of the use of resources, namely labour and mechanized works, will be analysed according to the crop system to see whether the transition to sustainable agriculture is economically viable.
Keywords: Q12; 330; labour productivity; oil plants; conventional; ecological